Konsep dan Urgensi Demokrasi yang Bersumber dari Pancasila - Bambang Trisno; Oti Aprillia; Oriza Latifah; Deyaninda Safira; Tasya Amanda Putri (Badan Penerbit STIEPARI Press, 2024)
Pancasila as the basis of the Indonesian state contains fundamental values ​​that reflect the aspirations and ideals of the nation. In the context of democracy, Pancasila emphasizes the importance of people's sovereignty, social justice, and respect for human rights. The concept of democracy originating from Pancasila prioritizes deliberation and consensus, which reflects a culture of mutual cooperation and kinship. The urgency of Pancasila democracy lies in its ability to maintain diversity, maintain unity, and ensure transparent and accountable government. Thus, the implementation of democracy based on Pancasila can be a solution to various political and social challenges in Indonesia, as well as creating a more just and prosperous social order.